The Effect of Spin-Orbit Interaction On Structural and Electronic Properties of ScIr2 - Huseyin Yasin Uzunok (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
The structural and electronic properties of face-centred cubic ScIr2 compound is investigated by using a generalised gradient approximation scheme of density functional theory with and without spin-orbit interaction. The structural results show that the spin-orbit interaction has a negligible effect for the crystallizing of ScIr2 compound. The Fermi surface calculations suggest considerable nesting along Γ-X direction that could affect the vibrational properties.